MORPHOMETRIC STUDY OF MITRAL VALVE IN HUMAN HEARTS – A COMPARATIVE ANATOMICAL STUDY - DR. B. SENTHIL KUMAR; DR. A. ANAND (International Journal of Pharma and Bio Sciences, 2013)
Heart disease is one of the major causes for mortality and morbidity in our country. Cardiac valvular anomalies and abnormalities form an important factor for heart disease. The incidence of Mitral Valve Prolapse Syndrome is a silent contributor to the increasing statistics of heart disease. The aim of the study is to measure the dimensions of the mitral valve in cadaveric human hearts and compare it with autopsied heart specimens. The study involves 45 cadaveric and 15 autopsy heart specimens. The left atrium and left ventricle were cut open and valves were examined and measurements of the Mitral valves were taken using Vernier caliper. The circumference and area of mitral annulus differs by 1 cm in cadaveric heart specimens from autopsied heart specimens due to the effect of fixation whereas the annular diameter more or less equal in both specimens. The maximum length of leaflets of all cusps was high in autopsied hearts when compared with that of cadaveric hearts. The leaflet attachment of cusp was found to be high in cadaveric hearts than the autopsied heart. The present study findings of autopsied heart specimens can be applied to improve several surgical repair techniques and in valvular replacements.